Regime-dependent impulse response functions in a Markov-switching vector autoregression model - Michael Ehrmann; Martin Ellison; Natacha Valla (Bank of Finland, 2001)
In this paper we introduce identifying restrictions into a Markov-switching vector autoregression model.We define a separate set of impulse responses for each Markov regime to show how fundamental disturbances affect the variables in the model dependent on the regime.We go to illustrate the use of these regime-dependent impulse response functions in a model of the U.S. economy.The regimes we identify come close to the "old" and "new economy" regimes found in recent research.We provide evidence that oil price shocks are much less contractionary and inflationary than they used to be.We show furthermore that the decoupling of the US economic performance from oil price shocks cannot be explained by "good luck" alone, but that structural changes within the US economy have taken place.
URN:NBN:fi:bof-20140807559
Keywords: 330; vector autoregression; regime switching; shocks; new economy